A Novel Pain Interprofessional Education Strategy for Trainees: Assessing Impact on Interprofessional Competencies and Pediatric Pain Knowledge - Judith P. Hunter; Jennifer Stinson; Fiona Campbell; Bonnie Stevens; Susan J. Wagner; Brian Simmons; Meghan White; Margaret van Wyk (Pain Research and Management)
BACKGROUND: Health care trainees/students lack knowledge and skills for the comprehensive clinical assessment and management of pain. Moreover, most teaching has been limited to classroom settings within each profession.